Analysis of deformation and failure characteristics of rock anchor foundations in limestone strata of southern Anhui mountainous areas - Jiaming, Jiang; Weidong, Cheng; Xiaodong, Cheng; Qiuyang, Hong; Zhou, Yang (Frontiers in Materials, 2025)
This study investigates the deformation and failure mechanisms of rock anchor foundations within the limestone strata characteristic of southern Anhui’s mountainous regions. The research aims to establish quantitative design thresholds to enhance the safety and efficiency of engineering projects in these geologically complex areas.A multi-scale methodology was adopted, integrating field pull-out tests, laboratory experiments on rock-grout interfaces, and detailed numerical simulations. This comprehensive approach enabled a systematic analysis of the anchorage system’s behavior under various loading conditions and geometric configurations.The core findings provide critical quantitative benchmarks. A critical anchorage depth of approximately 3,500 mm was identified, which delineates a shift in failure mode. At depths shallower than 3,000 mm, failure occurs primarily by pull-out along the rock-grout interface. Beyond 4,000 mm, the failure mode transitions to tendon extraction from the grout column, with the peak pull-out capacity observed at the 3,000 mm depth. For group anchor systems in a 2 × 2 configuration, the ultimate pull-out capacity reached 3600 kN, representing a four-fold increase over a single anchor, attributable to stress superposition effects. An embedded rock depth of 400 mm was determined to be the optimal threshold for maximizing structural ductility. Furthermore, parameter sensitivity analysis established an optimal diameter ratio criterion (D/d > 3.2) as the most significant parameter for optimizing pull-out performance.The results demonstrate that anchorage depth, group effect, and the diameter ratio are pivotal factors controlling the performance of rock anchor foundations in limestone. The identified thresholds and failure mode transitions provide crucial insights for design. These quantitative findings offer direct theoretical support and a practical basis for the design optimization of rock anchor foundations under similar geological conditions.